Goss Community Offset Machine Wiring Panel Image (Paper): Gambar Wiring Panel Mesin Offset Goss Community (Kertas) - Rossoleh, Andriyan Herqi; Wisaksono, Arief (Procedia of Engineering and Life Science, 2024)
Abstract. Review control activities, especially reducing the quality of printouts on Goss Community offset machines, are one of the quality control parameters carried out by each company. The Goss Community offset machine panel itself is usually equipped with various buttons, settings and monitors that allow the operator to control various print parameters, such as print speed, starting and stopping the machine, and so on. In this article we discuss the understanding of the components of the Goss Community offset machine panel and drawing the wiring panel of the Goss Community offset machine itself. The process of drawing the offset machine panel wiring is done by drawing the monitor panel and drawing the wiring from the PWM control, to study the offset panel. from drawing wiring in AutoCAD to assembly. And understanding of components such as MCB, contractor, power supply, relay, pwm, plc, scr, diode, busbar. Drawing components using AutoCAD allows a better understanding of their design and functionality.Keywords - Quality, Parameters, wiring drawing, components Web Offset Goss Community